The Role of Digitalization in Data-Driven Decision Making in Supply Chain Management - I. G. Kamenev; D. A. Porohovnik (Управленческие науки, 2025)
The article presents the results of a study aimed at identifying the current and potential roles of digital platforms in supply chain management. The research reviews existing theoretical approaches and developments in this area, as well as analyzes case studies of successful digitalization. The authors demonstrate how the transition of digital platforms to working with Big Data sources is transforming their role in the management process. Previously, at the stage of digital reporting, there was a gap between operational logistics functional management and expert analytical work with aggregated indicators. However, new systems that provide for the processing, storage, and analysis of data, as well as the visualization of this information and the results of its analysis, make it possible to link strategic goal-setting, KPIs, and supply chain resilience management directly with data flows about functional business processes, creating a “digital twin” of the enterprise. Using structural-functional analysis and the case study method, the study examines management practices synthesizes a comprehensive approach to exploring the interrelation between technological and managerial innovations during the implementation of digital platforms. As a result, the paper proposes a model that outlines the role of digital platforms at different levels of management activity. It distinguishes between technological innovations (the development of digital platforms tailored to organizational needs) and managerial innovations (adaptive development of data-driven organizational management systems). The findings may be of interest both to academic researchers studying management challenges amid digital transformation and to practitioners conducting applied scientific and analytical studies of digital transformation outcomes in the express delivery industry and related sectors.